2006
DOI: 10.1017/s1464793105006998
|View full text |Cite
|
Sign up to set email alerts
|

Thermal behaviour of crustaceans

Abstract: Specific thermoreceptors or putative multimodal thermoreceptors are not known in Crustacea. However, behavioural studies on thermal avoidance and preference and on the effects of temperature on motor activity indicate that the thermosensitivity of crustaceans may be in the range 0.2-2 degrees C. Work on planktonic crustaceans suggests that they respond particularly to changes in temperature by klinokinesis and orthokinesis. The thermal behaviour of crustaceans is modified by thermal acclimation among other fac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
63
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(71 citation statements)
references
References 146 publications
4
63
0
Order By: Relevance
“…In contrast, during active periods, crayfish select warmer temperatures, increasing metabolic energy expenditure, with a trade-off being an increased predation risk as the crayfish that have burrowed congregate with other crayfish in shallower waters. Thus, it appears that the detection and selection of temperature is an important eco-physiological trait in P. clarkii and, presumably, other crayfish (Lagerspetz and Vainio, 2006). In the present study, we demonstrated that P. clarkii learn to thermoregulate behaviourally within a dual-choice shuttlebox.…”
Section: Thermoregulation In Crayfishsupporting
confidence: 56%
“…In contrast, during active periods, crayfish select warmer temperatures, increasing metabolic energy expenditure, with a trade-off being an increased predation risk as the crayfish that have burrowed congregate with other crayfish in shallower waters. Thus, it appears that the detection and selection of temperature is an important eco-physiological trait in P. clarkii and, presumably, other crayfish (Lagerspetz and Vainio, 2006). In the present study, we demonstrated that P. clarkii learn to thermoregulate behaviourally within a dual-choice shuttlebox.…”
Section: Thermoregulation In Crayfishsupporting
confidence: 56%
“…Temperature selection was observed in many benthic and planktonic crustaceans (Lagerspetz & Vainio, 2006). Usually, it is based on changes in activity and movement speed rather than on a directional taxis (Lagerspetz & Vainio, 2006).…”
Section: Experiments 2: Current Velocitymentioning
confidence: 99%
“…Temperature may vary vertically due to the stratification of the water column, as well as horizontally and temporally in shallow waters, affected by shading and solar radiation (Lagerspetz & Vainio, 2006). For alien species, temperature can be the most important environmental factor determining the possibility of survival, reproduction and establishment in the new area in the case of climatic differences between the donor and recipient regions (Müller & Baur, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…2, which showed little capacity for survival at temperatures different than 10°C, maintained a similar locomotor activity at temperatures ranging from 7 to 16°C. In addition to the technical challenge of accurately measuring the movement of these 5-mm-long arthropods in the dark, and despite numerous studies using locomotor activity as a proxy of isopods' performance (Lagerspetz and Vainio, 2006;Dailey et al, 2009;Schuler et al, 2011), mean velocity did not appear to be a pertinent indicator of the performance in Proasellus species for at least two reasons. First, mean velocities were extremely low (between 1 and 8cmmin…”
Section: Temperature (°C)mentioning
confidence: 99%